Unusual and interesting adverse cutaneous drug reactions - Vaishali Masatkar; Ashok Nagure; Lalit Kumar Gupta (Wolters Kluwer Medknow Publications, 2018)
Any drug can cause any rash! Cutaneous adverse drug reactions (CADRs) are great mimickers and can be included in the differential diagnosis of any inflammatory dermatoses. Several drugs can cause rash of similar morphology and the same drug can cause rash of different morphology. While some common and specific drug reaction patterns are recognized easily by the clinicians, many a times unusual and interesting patterns can be induced by drug(s), thus leading to erroneous diagnosis and mistreatment. This review aims to familiarize clinicians with some rare, yet interesting patterns of CADR.